Mathematical Model of Simultaneous Flow between Casson Fluid and Dust Particle over a Vertical Stretching Sheet - Mohd Kasim, Abdul Rahman; Arifin, Nur Syamilah; Arifin, Nur Syamilah; Ariffin, Noor Amalina Nisa; Salleh, Mohd Zuki; Anwar, Muhammad Imran (International Journal of Integrated Engineering, 2020)
The process involving multiphase flow generally can be found in natural phenomena and many industrial applications. It might be between solid-liquid flow, liquid-liquid flow, gas-solid flow or gas-liquid flow. Their interaction is significant and able to influence the flow characteristics. The experimental work for this topic has been widely performed in order to obtain the best interaction output but it is still incomplete due to the limitation in term of cost and safety issue. Since then, the mathematical model is proposed to counter that constraint. This paper is aims to propose the mathematical model representing the two-phase flow which the interaction of non-Newtonian Casson fluid and solid particles is examined. The flow is investigated moving over a stretching sheet and the combined convection is considered together with the influence of heat generation in fluid phase. The governing equations representing the two-phase model are first transformed into the ordinary differential equations using established similarity transformations where the complexity of the model is reduced. The resulting equations are then solved by employing the Keller-box method with the help of Matlab software. The numerical output in term of velocity and temperature distribution for both phases are illustrated graphically and the value of skin friction and heat transfer coefficients are presented in tabular form for various value of mixed convection parameter, heat generation parameter and Casson parameter. Findings reveal that, the parameter under investigation affects the flow characteristics and present a significant impact to both phases except for mixed convection parameter.